2021
DOI: 10.3390/cells10123311
|View full text |Cite
|
Sign up to set email alerts
|

Acidic and Hypoxic Microenvironment in Melanoma: Impact of Tumour Exosomes on Disease Progression

Abstract: The mechanisms of melanoma progression have been extensively studied in the last decade, and despite the diagnostic and therapeutic advancements pursued, malignant melanoma still accounts for 60% of skin cancer deaths. Therefore, research efforts are required to better define the intercellular molecular steps underlying the melanoma development. In an attempt to represent the complexity of the tumour microenvironment (TME), here we analysed the studies on melanoma in acidic and hypoxic microenvironments and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 148 publications
0
9
0
Order By: Relevance
“…Acidity is a unique hallmark of the tumor microenvironment. Many pH-sensitive nanomedicines were designed and prepared to respond to the acidic tumor microenvironment promoting antitumor efficiency. Inorganic nanomaterials, which possess a diverse range of structure, composition, morphology, and physicochemical properties have been used in cancer treatment and diagnosis as delivery carriers. Recently, various metal oxides or calcium-based nanomaterials have been widely used as pH-sensitive inorganic nanomaterials. It has been reported that ZnO NPs could be used as pH-responsive drug carriers, which possess pH-triggered drug release characteristics displaying a response to acid and a rapid dissolution to Zn 2+ at pH <5.5, especially in lysosomes used for intracellular drug delivery platforms. The intracellular Zn 2+ produced by ZnO NPs has cytotoxic effects in tumor cells. , In addition, ZnO NPs could significantly induce the generation of ROS in tumor cells. In particular, ZnO NPs can make full utilization of disproportional reaction, Haber–Weiss reaction, or Fenton reaction to compensate for O 2 -depletion, thus greatly improving the therapeutic efficacy against hypoxic tumors . ZnO NPs also have good optical properties and high stability to be a promising candidate for bioimaging. , ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism for tumor imaging. , Recently, we designed an H 2 O 2 -triggered intelligent photodynamic therapy (PDT) nano delivery system, LCL/ZnO, that could selectively regulate the tumor-derived endothelial cells (TECs) and specifically kill tumor cells by producing different singlet oxygen ( 1 O 2 ) in response to different H 2 O 2 gradients in TECs and tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Acidity is a unique hallmark of the tumor microenvironment. Many pH-sensitive nanomedicines were designed and prepared to respond to the acidic tumor microenvironment promoting antitumor efficiency. Inorganic nanomaterials, which possess a diverse range of structure, composition, morphology, and physicochemical properties have been used in cancer treatment and diagnosis as delivery carriers. Recently, various metal oxides or calcium-based nanomaterials have been widely used as pH-sensitive inorganic nanomaterials. It has been reported that ZnO NPs could be used as pH-responsive drug carriers, which possess pH-triggered drug release characteristics displaying a response to acid and a rapid dissolution to Zn 2+ at pH <5.5, especially in lysosomes used for intracellular drug delivery platforms. The intracellular Zn 2+ produced by ZnO NPs has cytotoxic effects in tumor cells. , In addition, ZnO NPs could significantly induce the generation of ROS in tumor cells. In particular, ZnO NPs can make full utilization of disproportional reaction, Haber–Weiss reaction, or Fenton reaction to compensate for O 2 -depletion, thus greatly improving the therapeutic efficacy against hypoxic tumors . ZnO NPs also have good optical properties and high stability to be a promising candidate for bioimaging. , ZnO NPs could be used to in situ upconvert NIR to visible light through the second harmonic generation (SHG) mechanism for tumor imaging. , Recently, we designed an H 2 O 2 -triggered intelligent photodynamic therapy (PDT) nano delivery system, LCL/ZnO, that could selectively regulate the tumor-derived endothelial cells (TECs) and specifically kill tumor cells by producing different singlet oxygen ( 1 O 2 ) in response to different H 2 O 2 gradients in TECs and tumor cells .…”
Section: Introductionmentioning
confidence: 99%
“…Fibroblasts accumulate in the TME and contribute to the emergence and progression of GC [ 19 , 20 ]. This not only provides abundant growth factors for stromal components of the TME and promotes the proliferation of cancer cells but also creates a suitable physical environment for lymphatic metastasis and blood metastasis of cancer cells [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma-derived exosomes containing miR-155 and miR-210 were shown to reprogram dermal fibroblasts by increasing aerobic glycolysis and reducing oxidative phosphorylation, which led to extracellular acidification [ 62 ]. The role played by melanoma-derived EVs under acidic and hypoxic conditions has been recently reviewed [ 63 ].…”
Section: Role Of Evs In Melanoma Progressionmentioning
confidence: 99%